Answer:
see explanation
Step-by-step explanation:
(a)
Given f( x) = 3x + 4 then to find f(k) substitute x = k into f(x), that is
f(k) = 3k + 4
Now f(k) = k, thus
3k + 4 = k ( subtract 4 from both sides )
3k = k - 4 ( subtract k from both sides )
2k = - 4 ( divide both sides by 2 )
k = - 2
---------------------------------------------------------
(b)
let y = f(x) and rearrange making x the subject
y = 3x + 4 ( subtract 4 from both sides )
y - 4 = 3x ( divide both sides by 3 )
[tex]\frac{y-4}{3}[/tex] = x
Change y back into terms of x, thus
[tex]f^{-1}[/tex](x) = [tex]\frac{x-4}{3}[/tex]